قضية الشك في الشعر الجاهلي وعلاقتها بالإعجاز القرآني عند الشيخ محمود محمد شاكر - زيد, اعمارة; عزوز, ربيعة; شويخ, سعدية; لجدل, مريم (جامعة الوادي university of eloued, 2019)
الشعر، الإعجاز، القرآن، ثلاثة مصطلحات خاض فيها القدامى والمعاصرون من مستشرقين ومن حذا حذوهم، وخاصة أن في الشعر قضية شائكة ترتبط ارتباطا وثيقا بالإعجاز القرآني، ألا وهي قضية الشك في الشعر الجاهلي، ومن هذا الباب، فتح المستشرقون بابا للقدح في الإعجاز حيث قاموا بدراسات مزيفة كان همها الوحيد التنقيص من موروث العرب الذي هو ديوانهم و أرادوا منه وسيلة للقدح في نبوة محمد صلى الله عليه وسلم الذي معجزته القرآن، ووجه إعجاز القرآن المقصود هو الإعجاز البياني الذي أعجز العرب، ومن هنا سار الباحثون، في دراسة هذه الإشكالية، ومن بينهم شيخنا القدير محمود محمد شاكر الذي سخر وقته في إبراز هذه العلاقة التي تربط بين الإعجاز والقرآن وقد التجأ لمنهج كان سنده طيلة دراساته وسماه منهج التذوق حيث استقرا جميع ما وقع تحت يديه من كتب التراث دارسا ومحققا فوجد أن الشعر له علاقة وطيدة بالإعجاز القرآني وذلك أن القرآن نزل على العرب بلغتهم ولكن العرب عجزوا عن الإتيان بمثله لأنه ليس كلام بشر كما اعتقدوا بل هو كشاهد على القرآن والقرآن دليل على نبوة محمد صلى الله عليه وسلم. Summary Poetry، miracles، Quran، three terms used by the old and contemporary Orientalists and follow their example، especially in the hair is a thorny issue closely linked to the Quranic miracle، the question of doubt in the pre-Islamic poetry، and from this section، the Orientalists opened the door of the mug in the miracle where they With false studies، whose sole concern was to diminish the heritage of the Arabs، which is their religion. They wanted a way to mollify the prophecy of Muhammad (peace and blessings of Allah be upon him)، whose miracle is the Qur'an. Including our sheikh، the great Muhammad Shaker al Who ridiculed his time in highlighting this relationship between the miracles and the Koran has resorted to the curriculum was supported throughout his studies and called the method of taste، where he read all that happened under the hands of the books of heritage studying and verified that the poetry has a strong relationship Quranic miracle and that the Koran came down on the Arabs in their language، The Arabs were unable to do the same thing because it is not the word of men as they thought، but as a witness to the Quran and the Koran evidence of the prophecy of Muhammad peace be upon him.
لغة